Distribution characteristics of top SOC in different forest types of Genhe in the Greater Khingan Range of Inner Mongolia - Zhang, Jie; Song, Mingyue; Zheng, Shulin; Zhou, Pei; Guo, Jun; He, Junnan; Yue, Haijun (Scientific reports, 2025)
Soil serves as the largest active carbon reservoir in terrestrial ecosystems, playing a pivotal role in carbon sequestration. The study area is situated in Genhe City, on the western slope of the northern segment of the Greater Khingan Range in Inner Mongolia. We utilized a TOC/TN analyzer to measure the soil organic carbon (SOC) content and applied data analysis methods, including the coefficient of variation and the semivariogram function model, to examine the spatial distribution characteristics of SOC content in the surface layer. The results showed that the variation range of SOC content in the 0–5 cm and 5–10 cm soil layers of the four types of forest land sampling points is 100.98–327.59 g/kg and 44.22–322.71 g/kg. Within the same forest land, SOC content decreases with increasing soil depth. Overall, as latitude increases, the top SOC content shows an upward trend. However, in the Hanma region, the relationship between SOC content and latitude varies across different soil layers. This variation may be attributed to differences in vegetation, topography, and altitude. We believe that latitude, forest type, and altitude all influence the spatial distribution of SOC content. These findings provide a scientific basis and reference for establishing the spatial distribution patterns of top SOC content.